Biologia reprodutiva de cacau-jacaré (herrania mariae - sterculiaceae): III - comportamento dos insetos visitantes. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1995)
The Cocoa-Jacaré, a species phylogenetically close to the Cocoa (Theobroma cacao), has structurally complex flowers, which make spontaneous contact between its male and female parts unlikely and show an elaborate insect-mediated pollination mechanism. The most abundant insects among the visitors are, in order of abundance, those of the families Phoridae (Diptera), Staphilinidae (Coleoptera), Chloropidae (Diptera) and Formicidae (Hymenoptera). In the present work we define the behavioral patterns of each of these groups and evaluate the pollen carriage of Herrania mariae by these insects. Both field observations and pollen analyses indicated that Phoridae are the effective pollinators of this species. The behavior of the phorids, moving sequentially between the female and male parts of the flowers; the large amount of pollen carried by them during the visit; the pattern of visitation time coinciding with the period of greatest receptivity of the flower and the occurrence of pollination, added to some syndromes identified in the flower (such as the characteristic odor of flowers pollinated by flies) support our conclusions. All the phorids identified in this study are females of Dorniphora sp. This finding suggests the possibility of the existence of closer interaction mechanisms between this plant and its pollinators (MPEG/CNPq/CEPLAC).
Reproductive biology of cocoa (Herrania mariae - sterculiaceae): III - behavior of visiting insects.
Keywords: Herrania mariae; forídeos; Cacau-Jacaré; Reprodução; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA